a Literature review Performance assessment of nurse competence based on Electronic Nursing Logbook in Health Services - Budiani, Ni Putu Sri; Andriyanto, Arief (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
The era of industry 4.0, has developed an electronic logbook (E-logbook) which is used for more accurate documentation and assessing performance based on the achievement of each individual activity. The nurse's E-logbook is designed as a documentation that contains records of activity achievements, nurse skills, and updates of all activities, and is used in assessing employee behavior for one year. The purpose of this literature review is to determine whether the use of Electronic logbook has a significant impact on performance appraisal. The database search used included Google Scholar (40 articles), Pubmed (15 articles), and EBSCO (30 articles). The keywords used in the search for articles are electronic logbook, nurse, service quality, health services and only 5 articles were used that were suitable through analysis of objectives, topic suitability, research methods used, sample size, research ethics, results of each article, and limitations that occur. It was found that there was a positive impact on the use of electronic logbooks on clinical staff. The e-logbook continues to be updated to facilitate quantitative recording of the activities of each medical staff according to the details of their clinical authority and as a means of performance assessment